Analysis of Rahn Tasjily Financing Strategy Against Non Performing Financing (NPF) Members at Lumajang Branch KSPPS Syirkah Institution - Taufiq, Achmad; Hamdi, Muhammad; Rondik, Filip (Jurnal Iqtisaduna, 2025)
This study aims to analyze the NPF handling strategy, the causal factors, and its impact on the financial performance of cooperatives. Using a descriptive qualitative approach with secondary data from journals, books, and documents, this study identified that NPF in the Rahn Tasjily scheme was influenced by internal factors such as weak financing analysis and customer financial management, as well as external factors such as economic conditions and business failure. Handling strategies include intensive collection, financing restructuring, Jamkrida insurance, utilizing the PT CLIK application for credit detection, and issuing warning letters to confiscate collateral as a last resort. Member education and analysis strengthening based on the 5C principles and Sharia compliance were also applied to minimize risk. The study results indicate that this strategy effectively reduces NPF but requires regular supervision and ongoing education to ensure the sustainability of operations and member trust. This study provides insight for Islamic cooperative managers in managing financing risks.